1941
DOI: 10.1002/hlca.194102401171
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der Erythrophleum‐Alkaloide. (5. Mitteilung). Identifizierung der niedermolekularen Spaltsäure des Coumingins

Abstract: Silbersalz in den Methylester ubergefuhrt. Nach zweimaligem Destillieren siedete die Hauptmenge desselben bei 178-180° (0,3 mm). Eine Mittelfraktion wurde analysiert. 4,350 mg Subst. gabcn 10,955 mg CO, und 3,37 mg H,O 12,86 mg Subst. wurdcn mit 2,4 em3 0,2-n. wassrigcr Xatrcinlauge 2 Stundcn gekocht, wobei allmahlich Auflosung eintritt. Verbraucht wurden 0.360 cm3 dicser Laugc. C2,H,,0, Bcr. C 68,53 H 8,62% Yz Mo1.-Gcw. 175,l Gef. ,, 68,73 ., 8,67% ,. ., 178,6 Beim Vcrscifen mit alkoholischer Lauge konntcn wc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1941
1941
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…These authors further suggested that erythrophleic acid was a derivative of 1,7 ,8 -tri methylphenanthrene. Ruzicka, Dalma, and their associates (68,69,70) appear to have arrived, with much reluctance, at a similar conclusion with cassaine, ca ' ssaidine, loids will remain as subjects of chemical and pharmacological in vestigation for some time to come.…”
Section: Venommentioning
confidence: 99%
“…These authors further suggested that erythrophleic acid was a derivative of 1,7 ,8 -tri methylphenanthrene. Ruzicka, Dalma, and their associates (68,69,70) appear to have arrived, with much reluctance, at a similar conclusion with cassaine, ca ' ssaidine, loids will remain as subjects of chemical and pharmacological in vestigation for some time to come.…”
Section: Venommentioning
confidence: 99%
“…The 7α-H signal appears as a doublet (J = 8-10 Hz) at δ 3.87-3.95 and the 5α-H signal appears as a singlet at δ 2.28-2.66, if a 7β-hydroxy-6-keto group exists [15,23]. When 6β, 7β-dihydroxyl occurs, the 6α-H signal appears as a 13 C NMR Spectroscopy: Since most of the cassainetype diterpenoid ester amines and amides were obtained during the 1960s and 1970s, their 13 C-NMR properties have been little studied. However, the following conclusions can be made according to current knowledge.…”
Section: H Nmr Spectroscopymentioning
confidence: 99%
“…The three downfield carbonyl signals at δ 208-210, δ 167-170 and δ 173-177, together with the upfield methyl signal at δ 50-52, are attributed to, respectively, the carbonyl of the 6-or 7-keto group, the carbonyl of the C-16 ester or amide group, and the carbonyl and methyl of the C-4β carbomethoxy group [23]. 13 C-NMR spectra of ester amines differ from those of amides in signals of two methylene groups and the methyl linked with the N-atom in the N-containing side chain. For ester amines, the methylene signals appear at δ 58-60 and δ 46-48, attributed, respectively, to the methylene groups linked with the O-and N-atoms in the side chain; the signal of the methyl linked with N appears at δ 31-32.…”
Section: H Nmr Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations